HARmonized Protocol Template to Enhance Reproducibility of hypothesis evaluating real‐world evidence studies on treatment effects: A good practices report of a joint ISPE/ISPOR task force. Issue 1 (10th October 2022) - Wang, Shirley V.; Pottegård, Anton; Crown, William; Arlett, Peter; Ashcroft, Darren M.; Benchimol, Eric I.; Berger, Marc L.; Crane, Gracy; Goettsch, Wim; Hua, Wei; Kabadi, Shaum; Kern, David M.; et al.
Abstract: Problem: Ambiguity in communication of key study parameters limits the utility of real‐world evidence (RWE) studies in healthcare decision‐making. Clear communication about data provenance, design, analysis, and implementation is needed. This would facilitate reproducibility, replication in independent data, and assessment of potential sources of bias. What We Did: The International Society for Pharmacoepidemiology (ISPE) and ISPOR–The Professional Society for Health Economics and Outcomes Research (ISPOR) convened a joint task force, including representation from key international stakeholders, to create a harmonized protocol template for RWE studies that evaluate a treatment effect and are intended to inform decision‐making. The template builds on existing efforts to improve transparency and incorporates recent insights regarding the level of detail needed to enable RWE study reproducibility. The overarching principle was to reach for sufficient clarity regarding data, design, analysis, and implementation to achieve 3 main goals. One, to help investigators thoroughly consider, then document their choices and rationale for key study parameters that define the causal question (e.g., target estimand), two, to facilitate decision‐making by enabling reviewers to readily assess potential for biases related to these choices, and three, to facilitate reproducibility. Strategies to Disseminate and Facilitate Use: Recognizing that the impact of this harmonized template relies on uptake, we have outlined a plan to introduce and pilot the template with key international stakeholders over the next 2 years. Conclusion: The HARmonized Protocol Template to Enhance Reproducibility (HARPER) helps to create a shared understanding of intended scientific decisions through a common text, tabular and visual structure. The template provides a set of core recommendations for clear and reproducible RWE study protocols and is intended to be used as a backbone throughout the research process from developing a valid study protocol, to registration, through implementation and reporting on those implementation decisions.